2010
DOI: 10.1007/s10495-010-0490-z
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of dying cells: influence of smoking and static magnetic fields

Abstract: It is becoming evident that failure in the removal of dying cells causes and/or promotes the onset of chronic diseases. Impairment of phagocytosis of apoptotic cells can be due not only to genetic or molecular malfunctioning but also to external/environmental factors. Two of these environmental factors have been recently reported to down regulate the clearance of apoptotic cells: cigarette smoke and static magnetic fields. Cigarette smoke contains highly reactive carbonyls that modify proteins which directly/i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 207 publications
0
10
0
Order By: Relevance
“…Similarly, in this study, we observed an inversed correlation of pro-inflammatory COX-2 and prostaglandin expression with attenuated phagocytosis of 647-fAβ 42 in EMF-stimulated N9 cells. In support of this, down-regulated phagocytosis of latex particles or apoptotic cells has also been observed in other members of the mononuclear phagocyte system, such as macrophages and monocytes, in the presence of static magnetic fields (SMFs) [4244]. These decreased phagocytic activities were concomitant for driving the expressions of molecular components of various signaling pathways and effector functions, especially intracellular free Ca 2+ ([Ca 2+ ] i ), in the presence of SMFs [42, 44].…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, in this study, we observed an inversed correlation of pro-inflammatory COX-2 and prostaglandin expression with attenuated phagocytosis of 647-fAβ 42 in EMF-stimulated N9 cells. In support of this, down-regulated phagocytosis of latex particles or apoptotic cells has also been observed in other members of the mononuclear phagocyte system, such as macrophages and monocytes, in the presence of static magnetic fields (SMFs) [4244]. These decreased phagocytic activities were concomitant for driving the expressions of molecular components of various signaling pathways and effector functions, especially intracellular free Ca 2+ ([Ca 2+ ] i ), in the presence of SMFs [42, 44].…”
Section: Discussionmentioning
confidence: 83%
“…Based on advanced studies of SMF effects on oxidative stress reactions, the potentially hazardous effect of SMF on living organisms is that exposure to SMF can increase the activity, concentration, and life time of paramagnetic free radicals, which might cause oxidative stress, genetic mutation, and/or apoptosis (Mohtat et al 1998;Zhang et al 2003;Okano 2008;Dini 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Damage to lymphocytes by SMF (7 mT) increased up to 20% when they were treated with ferrous chloride (FeCl2) (Zmyslony et al, 2000;Junji, 2006). Moreover, exposure to SMF could increase the activity, concentration and lifetime of paramagnetic free radicals, leading to oxidative stress, genetic mutation and apoptosis (Zhao, 2011;Dini, 2010), and exposure to SMF initiates an ironmediated process that increases free radical formation in brain cells, leading to the breaking of DNA strands and cell death (Soumaya et al, 2013).…”
Section: Discussionmentioning
confidence: 99%